A REVIEW ON EVALUATION OF CRACK SIZE AND CRACK LOCATION ON CRACKED BEAM STRUCTURE USING FUZZY LOGIC TECHNIQUE - Vikram Yendhe; Prof. V.L Kadlag (International Journal of Innovations in Engineering Research and Technology, 2021)
Early detection of damage is of special concern for engineering structures. The traditional methods of damage detection include visual inspection or instrumental evaluation. A comparatively recent development for the diagnosis of structural crack location and size by using the finite element method and Fuzzy logics techniques. A method based on measurement of natural frequencies is presented for detection of the location and size of a crack in a cantilever beam. Here FEM software package is used for finite element analysis of both crack and un-crack cantilever beam Experiments is done for total 9 models of crack beam having different crack location and crack depth and it generates natural frequency for 3 modes ofvibration. Fuzzy controller here used comprises of three input variables (fnf, snf, tnf) with Gaussian MF and two output variables (rcl, rcd) are generated with Triangular MF. The proposed approach has been verified by comparing results obtained from fuzzy logic technique and finite element analysis.